Integrating research using animal‐borne telemetry with the needs of conservation management. Issue 2 (11th August 2016) - McGowan, Jennifer; Beger, Maria; Lewison, Rebecca L.; Harcourt, Rob; Campbell, Hamish; Priest, Mark; Dwyer, Ross G.; Lin, Hsien‐Yung; Lentini, Pia; Dudgeon, Christine; McMahon, Clive; Watts, Matt; et al.
Summary: Animal‐borne telemetry has revolutionized our ability to study animal movement, species physiology, demography and social structures, changing environments and the threats that animals are experiencing. While there will always be a need for basic ecological research and discovery, the current conservation crisis demands we look more pragmatically at the data required to make informed management decisions. Here, we define a framework that distinguishes how research using animal telemetry devices can influence conservation. We then discuss two critical questions which aim to directly connect telemetry‐derived data to applied conservation decision‐making: (i) Would my choice of action change if I had more data? (ii) Is the expected gain worth the money and time required to collect more data? Policy implications . To answer questions about integrating telemetry‐derived data with applied conservation, we suggest the use of value of information analysis to quantitatively assess the return‐on‐investment of animal telemetry‐derived data for conservation decision‐making.